PENGARUH PERLAKUAN PENDAHULUAN PADA PEMBUATAN TEPUNG GANYONG (CANNA EDULIS) TERHADAP SIFAT FISIK DAN AMILOGRAFI TEPUNG YANG DIHASILKAN - Agus Slamet (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
Ganyong flour is product derived from ganyong crop (Canna edulis). However, its appearance looks a bit dull. With pretreatments blanching, submerging in salt water or bisulphide, it is expected that processing would yield (a) brighter flour. Wider use of ganyong flour other than conventional ones has not been attempted because of lack of information on its amilographical property. A research on this is therefore needed. Pretreatments vary from none serving as a check to blanching, submerging in salt water or bislphide. Ganyong flour produced from all processing was analyzed for its color, water absorbing capacity, and amilographical properties which include gelatination temperature, gelatination time, and peak viscosity at 50oC. Experimental yield showed that with treatments, ganyong flour produced is brighter than control. Water absorbing capacity of flour from processing with blanching pretreatment is 509,28% of dry weight. The amilographical properties are as follows : gelatination temperature and time are 76,05 oC and 32,82 minutes respectively, viscosity at peak and at 50 oC are 580and 370 Brabender Unit (BU).